ANALYSIS OF FACTORS AFFECTING COMPLIANCE WITH PAYING TAX ADMINISTRATION OF UMKM IN BOALEMO DISTRICT - Muhammad Riski; Wiliam Indra S. Mooduto; sukri anto (Journal of Economic, Business, and Administration (JEBA), 2023)
This study aims to determine the effect of supervision on UMKM billboard tax payment compliance in Boalemo Regency, to determine the effect of tax sanctions on MSMEs billboard tax payment compliance in Boalemo Regency, and to determine the effect of knowledge on UMKM billboard tax compliance. in Boalemo Regency. The method in this study uses a quantitative research approach with a descriptive research approach, the types and sources of data using qualitative data and quantitative data. The results of this study are supervision of 0.122 with a significant value of 0.745 which is greater than 0.05 in other words, the hypothesis is rejected, meaning that there is a negative and partially significant effect, no positive effect between the supervision variable on the advertising tax variable. The tax penalty variable is 3.002 with a significant value of 0.003. Thus, a significant value of 0.003 is smaller than 0.05, this means that this means that the hypothesis is accepted. In other words, there is a positive and partially significant effect between tax sanctions on Advertising Tax. The variable of taxation knowledge is 1.352 with a significant value of 0.180. a significant value of 0.180 is greater than 0.05, this means that the hypothesis is rejected, meaning that there is no negative and partially significant effect between the supervision of the advertisement tax